Evaluadores del Volumen 36(1) (RUNA, archivo para las ciencias del hombre, 2015)
Evaluadores Nacionales•     Adelaida Colángelo – UNLP, La Plata    •     Alejandro Isla – FLACSO•     Ana Guglielmucci – CONICET-UBA•     Axel Lazzari – UNSaM•     Beatriz Goldwaser – UNLu, Luján•     Carolina Duek – I.I.G.G., UBA•     María Carolina Feito – Facultad de Agronomía, UBA•     Eva Muzzoppapa – UNRN, Río Negro•     Gisella Cassiodoro – INAPL, CONICET•     Hernán Palermo – CEIL / CONICET•     Julieta Gómez Otero – CENPAT / CONICET / UNPSJ, Pto. Madryn, Chubut•     Maria Soledad Gheggi – CRILAR / CONICET, Anillaco, La Rioja•     Patricia Arenas – UNT / UNSE, Tucumán – Santiago del EsteroEvaluadores Extanjeros•     Gonzalo Figueiro – Universidad de la República del Uruguay, Uruguay•     Luciana Hartman – Universidade de Brasília, Brasil•     Marta Cioccari – Universidade Federal do Rio de Janeiro, Brasil